The effect of perceived organizational support to employee’s organizational commitment - Artatanaya, I Gusti Lanang Suta; Supiatni, Ni Nyoman; Kencanawati, A A Ayu Mirah; Marhaeni, Kadek Eni; Muderana, I Ketut (International research journal of management, IT and social sciences, 2023)
This study aims to determine the effect of perceived organizational support on employee organizational commitment. The number of samples used was 50 employees of MSMEs XYZ Denpasar through the saturated sample method. Data collection was carried out through interviews and questionnaires. The data analysis technique used is simple linear regression. The results of this study indicate that perceived organizational support has a positive and significant effect on organizational commitment. The results of this study have implications for the management of XYZ Denpasar to pay more attention to the indicators of perceived organizational support in order to increase employee organizational commitment.